Sand dune conservation, management and restoration - Doody, J. Patrick. (Coastal research library, 2013)
This book deals with the development of temperate coastal sand dunes and the way these have been influenced by human activity. The different states in which the habitat exists both for the beach/foredune and inland dune are reviewed against the pressures exerted upon them. Options for management are considered and the likely consequences of taking a particular course of action highlighted. These options include traditional approaches to the conservation and management of wildlife and landscapes as well as habitat restoration. The way the value of the areas changes under different management regimes is considered mainly from an environmental perspective. Consideration is given to new approaches to management and restoration including adopting a more dynamic approach. Audience This book will be of interest to academics, students and professionals concerned with policy formulation and /or actively managing coastal areas. Preface --  1. Introduction --  2. Human occupation, use and abuse -- 3. Nature conservation - policy and procedures -- 4. Physical states and values - beaches/foredune -- 5. Vegetated states and values -Inland Dune -- 6. Trends and trade-offs - beaches/foredune -- 7. Trends and trade-offs - Inland vegetated dune -- 8. Alien plant invasion -- 9. Management and restoration - applying best practice -- 10. Integrated action - Golf course management -- 11. Integrated action - machair, human history and nature intertwined -- 12. Present threats and future prospects -- Index.